Ответы и объяснения

2013-02-11T17:57:52+00:00

b)
sin206 * tg13 + cos 206 = -1
206=pi+26 =>
sin206=sin(pi+26)=-sin26
cos206=cos(pi+26)=-cos26
теперь:
sin206 * tg13=-sin26*tg13=-2sin13cos13*tg13=-2sin^2(13)=>
sin206 * tg13 + cos 206=-2sin^2(13)-cos26=-2sin^2(13)-1+2sin^2(13)=-1 что и требывалось доказать...
c)
cos68 * tg11 + sin68 = 1
68=90-22=>
cos68=sin22
sin68=cos22=>
sin22*tg11+cos22=1 аналогичное b)...
d)
sin242 * ctg31 - cos 242 = -1
242=pi+62=>
sin242=-sin62
cos242=-cos62=>
sin62*ctg31-cos62=1
2cos^2(31)-2cos^2(31)+1=1
1=1...
e)
cos78 * ctg6 - sin78 = 1
78=90-12=>
cos78=sin12
sin78=cos12=>
sin12*ctg6-cos12=1
2cos^2(6)-2cos^2(6)+1=1
1=1...

Лучший Ответ!
  • Ios
  • хорошист
2013-02-11T17:57:58+00:00